Models of concurrent program running in resource constrained environment - Rahozin, D. (Проблеми програмування, 2020)
The paper considers concurrent program modeling using resource constrained automatons. Several software samples are considered: real time operational systems, video processing including object recognition, neural network inference, common linear systems solving methods for physical processes modeling. The source code annotating and automatic extraction of program resource constraints with the help of profiling software are considered, this enables the modeling for concurrent software behavior with minimal user assistance.